The space of the university campus. A trajectory of spatialization of universities in Santiago, Chile - Martínez-Leiva, María José (CIAN-Revista de Historia de las Universidades, 2025)
This article examines the spatialization of university campuses in Santiago de Chile through a qualitative documentary analysis. Campuses, as key nodes within the city, shape the urban experience of academic communities and thus assume a central role in the production of urban space. Drawing on academic literature and official documents, the article identifies three historical phases in the process of university spatialization in Santiago: (1) the eighteenth and nineteenth centuries, marked by the emergence of the first university space in Chile; (2) the twentieth century, characterized by the consolidation of the campus as the dominant spatial form; and (3) the late twentieth century, when the proliferation of campuses functioned as a strategy of “urban acupuncture,” driven by the liberalization of the higher education market. The article highlights the relevance of a historiographical approach to university space, given that public policy instruments have not systematically monitored the presence of universities in the city. Consequently, it underscores the need to study the urban expressions of universities—that is, their campuses and their relations with their surroundings. In doing so, it becomes possible to interpret their current situation and anticipate their future role within the city.
Keywords: university campus; spatialization of the university; urban space; Santiago